Cerium-containing magnet with high efficient grain boundary diffusion and preparation method thereof

CN122991838APending Publication Date: 2026-10-27NINGBO JINJI STRONG MAGNETIC MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610761820.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-05-29
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

浙江东阳东磁稀土有限公司在专利CN202211521156.5中尝试将晶界扩散引入铈磁体,但其研究重点主要集中在扩散源成分的优化,未对扩散源、扩散工艺与含铈基体组织之间的匹配关系进行系统分析,导致对铈磁体晶界扩散效率的挖掘仍显不足

Benefits of technology

(1)本发明通过限定含铈基体中t1/t2=14.5~15.2,精准调控Fe、Co、B、Zr的配比,从成分根源上构建连续、均匀、低熔点的晶界扩散通道,避免CeFe2相过度聚集,大幅降低重稀土扩散阻力,为晶界高效扩散奠定结构基础。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122991838A_ABST
    Figure CN122991838A_ABST
Patent Text Reader

Abstract

本发明属于永磁材料技术领域,涉及一种晶界高效扩散的含铈磁体及其制备方法。所述制备方法包括以下步骤:渗透源合金粉末在含铈磁体基体材料表面进行晶界扩散处理,得到含铈磁体;含铈磁体基体材料的化学成分为[R1‑xCex]aM1bZrcBdCoeFe100%‑a‑b‑c‑d‑e,t1=Fe的重量份 / 55.845+Co的重量份 / 58.933,t2=B的重量份 / 10.811‑2×Zr的重量份 / 91.224,14.5≤t1 / t2≤15.2;渗透源合金粉末的化学成分为RHa1Ceb1Ga100%‑a1‑b1。通过基体成分、渗透源、扩散工艺的协同调控,制备了高丰度稀土磁体,降低成本,并提高磁体性能。
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of permanent magnet materials technology, and relates to a cerium-containing magnet with efficient grain boundary diffusion and its preparation method. Background Technology

[0002] In recent years, as the market for NdFeB permanent magnet materials has gradually become saturated, and the prices of key rare earth raw materials such as praseodymium, NdFeB, and dysprosium have continued to rise, companies have begun to promote sintered NdFeB magnets containing high-abundance rare earth elements lanthanum (La) and cerium (Ce) on a large scale in order to reduce production costs and achieve balanced utilization of rare earth resources. However, the introduction of lanthanum and cerium significantly deteriorates the coercivity performance of the magnets. How to increase their addition while further breaking through the upper limit of the overall performance of high-abundance rare earth permanent magnets has become one of the key research and development directions in the industry.

[0003] Current research on cerium-containing magnets mainly focuses on two directions: First, optimizing the microstructure of cerium magnets, with an emphasis on balancing the proportion of cerium added and the negative effects of the resulting CeFe2 on magnetic properties. For example, the Ningbo Institute of Materials Technology and Engineering, Chinese Academy of Sciences, proposed a dual-alloy process in patent CN202510304990.6, which optimizes the magnet's microstructure by introducing cerium-free alloy powder for doping modification, thereby improving magnetic properties. Second, applying grain boundary diffusion technology to the preparation process of cerium magnets. Zhejiang Dongyang Dongci Rare Earth Co., Ltd. attempted to introduce grain boundary diffusion into cerium magnets in patent CN202211521156.5, but its research mainly focused on optimizing the diffusion source composition, without systematically analyzing the matching relationship between the diffusion source, diffusion process, and cerium-containing matrix structure, resulting in insufficient exploration of the grain boundary diffusion efficiency of cerium magnets.

[0004] Existing research mostly pursues these two directions independently, lacking in-depth exploration of the synergistic control mechanism between matrix microstructure and diffusion process, making it difficult to achieve greater breakthroughs in the performance of cerium-containing magnets. How to deeply integrate the control of the microstructure of cerium magnet matrix with the design of diffusion source components and the optimization of diffusion process parameters to develop a method for preparing cerium-containing magnets with controllable microstructure, efficient grain boundary diffusion, and excellent overall performance has become a key technical challenge that urgently needs to be overcome in the development of high-abundance rare-earth permanent magnet materials. Summary of the Invention

[0005] To address the aforementioned problems in the prior art, the present invention aims to provide a cerium-containing magnet with efficient grain boundary diffusion and its preparation method, thereby overcoming the shortcomings of the prior art. The present invention employs the following technical solutions to achieve its objective: One aspect of the present invention provides a method for preparing a cerium-containing magnet with efficient grain boundary diffusion, comprising the following steps: A cerium-containing magnet matrix material is prepared; a permeation source slurry containing permeation source alloy powder is prepared; the permeation source slurry is coated onto the surface of the cerium-containing magnet matrix material to obtain an attached diffusion source magnet; the attached diffusion source magnet is subjected to grain boundary diffusion treatment, and then tempered to obtain the cerium-containing magnet with efficient grain boundary diffusion. The chemical composition of the cerium-containing magnet matrix material is expressed as [R] by weight percentage. 1-x Ce x ] a M1 b Zr c B d CoeFe 100%-a-b-c-d-e Wherein: 10wt%≤x≤20wt%, 29wt%≤a≤33wt%, 0wt%<b≤0.8wt%, 0.1wt%≤c≤0.3wt%, 0.91wt%≤d≤0.93wt%, 0wt%<e≤1wt%; R is one or both of Pr and Nd, and M1 is one or more of Cu, Ga, and Al; wherein the weight percentages of Fe, Co, B, and Zr satisfy the following relationship: t 1= Fe by weight / 55.845 + Co by weight / 58.933 t2 = (weight parts of B) / 10.811 - 2 × (weight parts of Zr) / 91.224 14.5≤t1 / t2≤15.2.

[0006] t1 represents the molar equivalent of the transition metals (Fe, Co), and t2 characterizes the equivalence relationship between B and Zr. This ratio determines the main phase (R2Fe) inside the magnet. 14 B) The proportion of rare-earth-rich grain boundary phases. When t1 / t2 is controlled within the above range, it can induce the formation of low-melting-point network channels in the grain boundary phase, while avoiding excessive segregation and aggregation of low-melting-point phases (such as CeFe2). This microstructure significantly reduces the resistance to subsequent heavy rare-earth infiltration and is a key foundation for ensuring the efficiency of subsequent grain boundary diffusion.

[0007] Preferably, the chemical composition of the permeation source alloy powder is expressed as RH by weight percentage. a1 Ce b1 Ga 100%-a1-b1The composition is as follows: 60wt%≤a1≤75wt%, 10wt%≤b1≤30wt%, 80wt%≤a1+b1≤95wt%, and RH is one or both of Dy and Tb. A certain proportion of Ce and Ga is innovatively introduced into the diffusion source containing heavy rare earth elements (Dy, Tb). The addition of Ce significantly improves the wettability and interfacial bonding between the infiltration source melt and the cerium-containing matrix grain boundaries; the addition of Ga effectively lowers the overall melting temperature of the infiltration source and improves the fluidity of the liquid phase. The synergistic effect of these three elements allows the heavy rare earth elements to smoothly penetrate deep into the magnet along the grain boundaries and form a dense, highly coercive shell on the surface of the main phase grains.

[0008] Preferably, the preparation process of the cerium-containing magnet matrix material includes: batching, melting to obtain a casting, hydrogen breaking of the casting to obtain coarse powder, air jet milling to obtain fine powder, orientation molding, and sintering.

[0009] More specifically, in the preparation process of the cerium-containing magnet matrix material, the melting step involves: a melting temperature of 1420~1470℃ and a casting temperature of 1400~1440℃; the hydrogenation step involves: the coarse powder obtained from hydrogenation having a D50 particle size of 220~400μm, a dehydrogenation treatment temperature of 400~550℃, and a time of 60~300min; the air jet milling step involves: grinding the coarse powder obtained from hydrogenation under inert gas protection using an air jet mill until the powder D50 particle size is 2~4μm; the orientation forming step involves: applying a 1.0~2.5T orientation magnetic field to the fine powder under inert protection, while simultaneously performing pressure forming at a forming pressure of 150~300MPa for 2~5s; and the sintering step involves: a sintering temperature of 1050~1100℃, a holding time of 3~10h, followed by vacuum self-cooling to 800~920℃ after the holding time, and then air cooling with inert gas.

[0010] Preferably, the permeation source alloy powder, thermoplastic resin binder, and organic solvent are mixed to form a permeation source slurry; based on the mass of the permeation source slurry, the amount of thermoplastic resin binder added is 2~5wt%, and the amount of organic solvent added is 10~20wt%.

[0011] Preferably, the preparation process of the permeation source alloy powder includes: batching, melting to obtain a casting, hydrogen breaking of the casting to obtain coarse powder, and air jet milling to obtain fine powder; the D50 particle size of the permeation source alloy powder is 2~5μm.

[0012] More specifically, in the preparation process of the permeation source alloy powder, the melting step has the following characteristics: the melting temperature is 1440~1490℃, and the casting temperature is 1410~1450℃; in the hydrogen annealing step, the coarse powder obtained by hydrogen annealing has a D50 particle size of 220~400μm, the dehydrogenation treatment temperature is 400~550℃, and the time is 60~300min; the air jet milling step includes: grinding the coarse powder obtained by hydrogen annealing into an air jet mill under inert gas protection until the powder D50 particle size is 2-3μm.

[0013] Preferably, the thermoplastic resin binder is one or more of polyvinyl butyral, polyvinyl acetal, and polyvinyl alcohol, and the organic solvent is one or more of esters, ketones, and alcohols.

[0014] Preferably, the amount of the permeation source slurry coating is 0.8 to 1.2 wt% of the weight of the cerium-containing magnet substrate material.

[0015] The grain boundary diffusion treatment employs a two-stage heating process: the first stage diffusion temperature is 900~950℃, and the holding time is 2~6h; subsequently, it is cooled to the second stage diffusion temperature of 800~850℃, and the holding time is 6~12h. The first stage is a relatively high-temperature, short-time treatment, which promotes the rapid melting of the penetration source of specific components and their rapid spread into the interior of the grain boundary in liquid phase form; the second stage is a low-temperature, long-time treatment, which allows the atoms that have entered the grain boundary to gradually move from the grain boundary into the interior of the main phase grains and redistribute uniformly.

[0016] Preferably, the tempering temperature is 460~550℃ and the holding time is 4~8h.

[0017] A second aspect of the present invention provides a cerium-containing magnet with efficient grain boundary diffusion, which is prepared by the above-described preparation method.

[0018] Compared with the prior art, the present invention has the following beneficial effects: (1) By limiting the ratio of Fe, Co, B and Zr in the cerium-containing matrix to t1 / t2=14.5~15.2, the present invention constructs a continuous, uniform, low-melting-point grain boundary diffusion channel from the composition source, avoids excessive aggregation of CeFe2 phase, greatly reduces the diffusion resistance of heavy rare earth, and lays the structural foundation for efficient grain boundary diffusion.

[0019] (2) This invention innovatively introduces Ce and Ga elements that match the matrix into the diffusion source by deeply integrating matrix regulation with diffusion source composition design. Compared with traditional single heavy rare earth diffusion sources, this RH-Ce-Ga ternary permeation source can significantly reduce the tension of the liquid phase interface, improve the wettability between the permeation source and the matrix, and promote the rapid and uniform diffusion of heavy rare earth ions in continuous grain boundaries.

[0020] (3) In the preparation process of the present invention, a two-stage grain boundary diffusion heat treatment process is preferred. The first stage is high-temperature rapid melting and penetration, and the second stage is low-temperature long time to promote the uniform redistribution of heavy rare earth elements; thus ensuring the microstructure of the magnet and the uniform diffusion distribution of the diffusion source.

[0021] (4) This invention prepares a high-abundance rare earth magnet with Ce addition of 10~20wt% by synergistic regulation of matrix composition, permeation source and diffusion process, thereby maximizing the utilization of high-abundance cerium, reducing the dependence on heavy rare earth and cost, and improving the magnet performance. The prepared magnet takes into account both low cost and high magnetic performance. Attached Figure Description

[0022] Figure 1 The images show the SEM images of the matrix magnetic material prepared in Example 1 and the magnet after infiltration of the matrix magnetic material, where (a) is the SEM image of the matrix magnetic material and (b) is the SEM image of the magnet after infiltration of the matrix magnetic material and a schematic diagram of EPMA point scanning. Figure 2 The images show SEM images of the matrix magnetic material prepared in Comparative Example 8 and the magnet after infiltration of the matrix magnetic material, where (a) is the SEM image of the matrix magnet. Figure 2 (b) shows the SEM image and EPMA point scan diagram of the magnet after infiltration of the matrix magnetic material; Figure 3 SEM image and EPMA point scan diagram of the substrate magnet prepared for Comparative Example 1; Figure 4 SEM image and EPMA point scan diagram of the substrate magnet prepared for Comparative Example 2; Figure 5 SEM images of the magnets after infiltration of the matrix magnetic material prepared for Comparative Examples 17, 18 and 19, wherein (a) is the SEM image of the magnet after infiltration of the matrix magnetic material of Comparative Example 17, (b) is the SEM image of the magnet after infiltration of the matrix magnetic material of Comparative Example 18, and (c) is the SEM image of the magnet after infiltration of the matrix magnetic material of Comparative Example 19. Detailed Implementation

[0023] In the description of this invention, unless otherwise stated, the numerical range "a~b" represents a shortened representation of any combination of real numbers between a and b, and includes both a and b. "Multiple" includes two or more types, and can be two, three, four, five, or more.

[0024] The technical solution of the present invention will be further described and illustrated below with reference to specific embodiments and accompanying drawings. It should be understood that the specific embodiments described herein are only for the purpose of helping to understand the present invention and are not intended to limit the specific scope of the present invention. Furthermore, the accompanying drawings used herein are merely for better illustrating the content disclosed in the present invention and do not limit the scope of protection. Unless otherwise specified, the raw materials used in the embodiments of the present invention are all commonly used in the art, and the methods used in the embodiments are all conventional methods in the art.

[0025] Example 1 The chemical composition of the matrix magnetic material of the cerium-containing magnet with high-efficiency grain boundary diffusion in this embodiment is expressed as follows (percentages are by weight): (Pr 20% Nd 80% ) 26.3% Ce 4.5% Cu 0.1% Ga 0.2% Zr 0.15% Al 0.2% Co 0.5% B 0.92% Fe 67.13% , where t1 is 1.211, t2 is 0.082, and t1 / t2 is 14.80.

[0026] The method for preparing the cerium-containing permeable magnet in this embodiment includes the following steps: S1: Weigh the raw materials according to the mass percentage of the above magnet components, and perform vacuum induction melting at a melting temperature of 1450℃. Cool down to 1430℃ and cast to obtain an alloy sheet. Place the alloy sheet in a hydrogen-crushing furnace for hydrogen-crushing treatment. The coarse powder obtained by hydrogen-crushing has a D50 particle size of 280μm. Then, perform vacuum dehydrogenation at 480℃ for 120min. Grind the coarse powder obtained by hydrogen-crushing into a nitrogen-protected air jet mill until the powder D50 particle size is 3.5μm. Apply a 2.0T orientation magnetic field to the fine powder under nitrogen protection, and simultaneously perform pressure molding at a molding pressure of 200MPa for 3s. Send the green blank into a vacuum sintering furnace for vacuum sintering with a vacuum degree ≤5×10 -3 Pa, heated to 1085℃ and held for 5 hours, after which vacuum self-cooled to 900℃, and then filled with high-purity argon for air cooling; a sheet-like cerium-containing magnet matrix material with dimensions of 40mm (length) × 40mm (width) × 3mm (height) was obtained.

[0027] S2: According to the weight percentage of alloy composition Dy 70 Ce 15 Ga 15(Element subscript values ​​are weight percentages) The ingredients were batched, smelted at 1480℃, and cast at 1450℃ to obtain a casting. The casting was hydrogen-crushed to obtain coarse powder with a D50 particle size of 300μm. Subsequently, it was vacuum dehydrogenated at 500℃ for 120min. The coarse powder obtained by hydrogen crushing was subjected to air jet milling under nitrogen protection to obtain alloy powder with a particle size of 2.5um.

[0028] S3: Add 3 wt% polyvinyl butyral as a binder and 20 wt% terpineol as an organic solvent to S2 alloy powder, mix evenly, and the alloy permeation source slurry is prepared.

[0029] S4: The alloy permeation source slurry obtained in S3 is uniformly coated onto the surface of the sheet-like cerium magnet substrate prepared in S1, with the coating amount accounting for 1.1 wt% of the substrate mass, to obtain a magnet blank with a diffusion source attached.

[0030] S5: The magnet blank with the diffusion source attached is placed in a heat treatment furnace. It is first heated to 920℃ at a heating rate of 6℃ / min and held for 4 hours. Then it is cooled to 820℃ at a rate of 10℃ / min and held for 8 hours for grain boundary diffusion treatment. Then it is cooled to 485℃ at a rate of 5℃ / min and held for 4.5 hours for tempering treatment. Finally, a cerium-containing magnet with efficient grain boundary diffusion is obtained.

[0031] Example 2 The chemical composition of the matrix magnetic material of the cerium-containing magnet with high-efficiency grain boundary diffusion in this embodiment is expressed as follows (percentages are by weight): (Pr 20% Nd 80% ) 25% Ce 6% Cu 0.2% Ga 0.18% Zr 0.2% Al 0.1% Co 0.4% B 0.915% Fe 67.005% , where t1 is 1.207, t2 is 0.08, and t1 / t2 is 15.04.

[0032] The method for preparing the cerium-containing permeable magnet in this embodiment includes the following steps: S1: Same as step S1 in Example 2.

[0033] S2: According to the weight percentage of alloy composition Dy 75 Ce 15 Ga 10(Element subscript values ​​are weight percentages) The ingredients were batched, smelted at 1470℃, and cast at 1440℃ to obtain a casting. The casting was hydrogen-crushed to obtain coarse powder with a D50 particle size of 320μm. Subsequently, it was vacuum dehydrogenated at 490℃ for 100min. The coarse powder obtained by hydrogen crushing was subjected to air jet milling under nitrogen protection to obtain alloy powder with a particle size of 2.7um.

[0034] S3: Add 3.5 wt% polyvinyl butyral as a binder and 15 wt% terpineol as an organic solvent to S2 alloy powder, mix evenly, and the alloy permeation source slurry is prepared.

[0035] S4: The alloy permeation source slurry obtained in S3 is uniformly coated onto the surface of the sheet-like cerium magnet substrate prepared in S1, with the coating amount accounting for 1.2 wt% of the substrate mass, to obtain a magnet blank with a diffusion source attached.

[0036] S5: The magnet blank with the diffusion source attached is placed in a heat treatment furnace. First, it is heated to 930℃ at a heating rate of 7℃ / min and held for 3 hours. Then, it is cooled to 810℃ at a rate of 11℃ / min and held for 10 hours for grain boundary diffusion treatment. Then, it is cooled to 480℃ at a rate of 6℃ / min and held for 5 hours for tempering treatment. Finally, a cerium-containing magnet with efficient grain boundary diffusion is obtained.

[0037] Example 3 The chemical composition of the matrix magnetic material of the cerium-containing magnet with high-efficiency grain boundary diffusion in this embodiment is expressed as follows (percentages are by weight): (Pr 20% Nd 80% ) 27.5% Ce 4% Cu 0.1% Ga 0.3% Zr 0.15% Al 0.35% Co 0.7% B 0.915% Fe 65.985% , where t1 is 1.193, t2 is 0.081, and t1 / t2 is 14.67.

[0038] The method for preparing the cerium-containing permeable magnet in this embodiment includes the following steps: S1: Same as step S1 in Example 2.

[0039] S2: According to the weight percentage of alloy composition Dy 65 Ce 20 Ga 15(Element subscript values ​​are weight percentages) The ingredients were batched, smelted at 1490℃, and cast at 1450℃ to obtain a casting. The casting was hydrogen-crushed to obtain coarse powder with a D50 particle size of 320μm. Subsequently, it was vacuum dehydrogenated at 520℃ for 100min. The coarse powder obtained by hydrogen crushing was subjected to air jet milling under nitrogen protection to obtain alloy powder with a particle size of 2.3μm.

[0040] S3: Add 4 wt% polyvinyl butyral as a binder and 18 wt% terpineol as an organic solvent to S2 alloy powder, mix evenly, and the alloy penetration source slurry is prepared.

[0041] S4: The alloy permeation source slurry obtained in S3 is uniformly coated onto the surface of the sheet-like cerium magnet substrate prepared in S1, with the coating amount accounting for 1.0 wt% of the substrate mass, to obtain a magnet blank with a diffusion source attached.

[0042] S5: The magnet blank with the diffusion source attached is placed in a heat treatment furnace. First, it is heated to 910℃ at a heating rate of 5℃ / min and held for 4 hours. Then, it is cooled to 830℃ at a rate of 9℃ / min and held for 8 hours for grain boundary diffusion treatment. Finally, it is cooled to 490℃ at a rate of 5℃ / min and held for 6 hours for tempering treatment, and finally, a cerium-containing magnet with efficient grain boundary diffusion is obtained.

[0043] Comparative Examples 1-11 Comparative Examples 1-11 differ from Example 1 only in the composition of the matrix magnetic material of the cerium-containing magnet. The specific weight percentage (wt%) is shown in Table 1. The preparation method is the same as that of Example 1.

[0044] Table 1. Composition of the matrix magnetic materials of cerium-containing magnets in Examples 1 and 10 (Comparative Examples 1-10) .

[0045] Comparative Example 11 The only difference between Comparative Example 11 and Example 1 is that in step S4 of Comparative Example 11, the coating amount of the alloy penetrating source slurry accounts for 1.4 wt% of the substrate mass. Everything else is the same as in Example 1.

[0046] Comparative Example 12 The only difference between Comparative Example 12 and Example 1 is that in step S4 of Comparative Example 12, the coating amount of the alloy penetrating source slurry accounts for 0.6 wt% of the substrate mass. Everything else is the same as in Example 1.

[0047] Comparative Example 13 The only difference between Comparative Example 13 and Example 1 is that the alloy composition of the permeation source in step S2 of Comparative Example 13 is Dy. 70 Pr 15 Ga 15(The element subscript values ​​are weight percentages). Everything else is the same as in Example 1.

[0048] Comparative Example 14 The only difference between Comparative Example 14 and Example 1 is that the alloy composition of the permeation source in step S2 of Comparative Example 14 is Dy. 70 Ce 15 Al 15 (The element subscript values ​​are weight percentages). Everything else is the same as in Example 1.

[0049] Comparative Example 15 The only difference between Comparative Example 15 and Example 1 is that the alloy composition of the permeation source in step S2 of Comparative Example 15 is Dy. 40 Ce 40 Ga 20 (The element subscript values ​​are weight percentages). Everything else is the same as in Example 1.

[0050] Comparative Example 16 The only difference between Comparative Example 16 and Example 1 is that the alloy composition of the permeation source in step S2 of Comparative Example 16 is Dy. 80 Ce5Ga 15 (The element subscript values ​​are weight percentages). Everything else is the same as in Example 1.

[0051] Comparative Example 17 The difference between Comparative Example 17 and Example 1 lies only in that step S5 of Comparative Example 17 specifically involves placing the magnet blank with the diffusion source attached in a heat treatment furnace, heating it to 920°C at a heating rate of 6°C / min and holding it at that temperature for 12 hours, then cooling it to 485°C at a rate of 5°C / min and holding it at that temperature for 4.5 hours for tempering treatment, ultimately obtaining a cerium-containing magnet with efficient grain boundary diffusion. Everything else is the same as in Example 1.

[0052] Comparative Example 18 The difference between Comparative Example 18 and Example 1 lies only in that step S5 of Comparative Example 18 is as follows: the magnet blank with the diffusion source attached is placed in a heat treatment furnace, first heated to 970°C at a heating rate of 6°C / min and held for 4 hours, then cooled to 820°C at a rate of 10°C / min and held for 8 hours for grain boundary diffusion treatment, and then cooled to 485°C at a rate of 5°C / min and held for 4.5 hours for tempering treatment, finally obtaining a cerium-containing magnet with efficient grain boundary diffusion. Everything else is the same as in Example 1.

[0053] Comparative Example 19 The difference between Comparative Example 19 and Example 1 lies only in that step S5 of Comparative Example 19 is as follows: the magnet blank with the diffusion source attached is placed in a heat treatment furnace, first heated to 880°C at a heating rate of 6°C / min and held for 4 hours, then cooled to 820°C at a rate of 10°C / min and held for 8 hours for grain boundary diffusion treatment, and then cooled to 485°C at a rate of 5°C / min and held for 4.5 hours for tempering treatment, finally obtaining a cerium-containing magnet with efficient grain boundary diffusion. Everything else is the same as in Example 1.

[0054] Comparative Example 20 The difference between Comparative Example 20 and Example 1 is only that: in Comparative Example 20, step S5 specifically involves placing the magnet blank with the diffusion source attached in a heat treatment furnace, first heating it to 920°C at a rate of 6°C / min and holding it there for 4 hours, then cooling it to 780°C at a rate of 10°C / min and holding it there for 8 hours for grain boundary diffusion treatment, and then cooling it to 485°C at a rate of 5°C / min and holding it there for 4.5 hours for tempering treatment, ultimately obtaining a cerium-containing magnet with efficient grain boundary diffusion. Everything else is the same as in Example 1.

[0055] Comparative Example 21 The difference between Comparative Example 21 and Example 1 lies only in that step S5 of Comparative Example 21 is as follows: the magnet blank with the diffusion source attached is placed in a heat treatment furnace, first heated to 920°C at a heating rate of 6°C / min and held for 4 hours, then cooled to 880°C at a rate of 10°C / min and held for 8 hours for grain boundary diffusion treatment, and then cooled to 485°C at a rate of 5°C / min and held for 4.5 hours for tempering treatment, finally obtaining a cerium-containing magnet with efficient grain boundary diffusion. Everything else is the same as in Example 1.

[0056] Magnetic performance test samples were prepared using wire cutting and end-face grinding processes. The sample size was 10 mm × 10 mm × 3 mm square pieces. Under room temperature (20℃) conditions, the magnetic properties of the cerium magnet substrates and their diffused magnets prepared in Examples 1-3 and Comparative Examples 1-21 were tested using an NIM-62000 demagnetization curve tester. The test results are listed in Table 2.

[0057] Table 2. Matrix magnetic material properties and infiltrated magnetic properties of the examples and comparative examples. .

[0058] Comparing Example 1 with Comparative Examples 5-16, it can be seen that, under the premise of roughly the same total amount of heavy rare earth elements, the cerium-containing magnet composition design, alloy infiltration source, and diffusion heat treatment process protected by this invention produce infiltrated magnets with significantly better absolute coercivity and infiltration improvement than the comparative examples. To further reveal the mechanism of performance improvement, the matrix and infiltrated magnets of Example 1 and Comparative Example 8 were characterized by scanning electron microscopy (SEM). Figure 1 , Figure 2 Compared to Comparative Example 8, the matrix magnetic material of Example 1 exhibits a more continuous, clear, and uniform grain boundary phase distribution with lower aggregation. This microstructure provides an efficient channel for subsequent grain boundary diffusion, a prerequisite for improving diffusion efficiency. The microstructure of the infiltrated magnet shows that Example 1 forms a clearer and more complete "core-shell" structure. Combined with the EDS point scan composition analysis in Table 3, the content of heavy rare earth element Dy in the epitaxial layer of the infiltrated magnet of Example 1 is significantly higher than that of Comparative Example 8. This indicates that the process of the present invention effectively promotes the diffusion of heavy rare earth elements along grain boundaries and their uniform distribution around the grains, which is the direct reason for the significant improvement in coercivity.

[0059] Table 3. External delay composition analysis of magnet grains after diffusion in Example 1 and Comparative Example 8

[0060] Comparing Example 1 with Comparative Examples 5-8 in Table 2, it can be seen that when the addition ratios of elements such as Co, Fe, B, and Zr exceed the t1 / t2 range defined in the claims, the increase in coercivity is significantly reduced even when using the same diffusion process. Comparing Example 1 with Comparative Examples 9-10 in Table 2, it can be seen that even if the components in the cerium-containing substrate are within their respective defined ranges, a final t1 / t2 ratio that is too low or too high is detrimental to subsequent diffusion. Through multiple sets of experiments, this invention verifies that when the t1 / t2 ratio is within the range defined in this invention, the grain boundary phase can form continuous and uniform low-melting-point channels, while avoiding excessive segregation and maximizing diffusion efficiency. The specific matrix composition design of this invention, especially the precise control of the t1 / t2 ratio, is the key foundation for ensuring the subsequent grain boundary diffusion efficiency.

[0061] Comparing Example 1 and Comparative Examples 1-2 in Table 2, it can be seen that, provided the basic composition meets the requirements, precise control of Ce content is crucial. When the Ce content is too low, the grain boundary phase distribution is unclear and the continuity is poor. Figure 3 This is because an appropriate amount of Ce can effectively lower the melting point of the grain boundary phase and improve fluidity; insufficient Ce cannot fully exert this effect, resulting in a microstructure unfavorable for penetration. When the Ce content is too high, the grain boundary phase exhibits obvious aggregation (…). Figure 4 The microstructure deteriorates, and the permeation resistance increases. (Refer to Table 4 for further details.) Figure 1 (a) Figure 3 , Figure 4 Point scan analysis showed that as the Ce content increased, the proportion of low-melting-point CeFe2 phase in the grain boundary phase increased significantly. An appropriate amount of CeFe2 phase helps to improve the grain boundary distribution (as in Example 1), but once the threshold is exceeded (as in Comparative Example 4), it will lead to excessive aggregation of the grain boundary phase, and the microstructure and magnetic properties will deteriorate sharply.

[0062] Table 4 Grain boundary phase composition of different Ce-added matrix magnetic materials

[0063] Comparing Example 1 with Comparative Examples 13-16 in Table 2, it can be seen that even when using a cerium-containing matrix with specific components of the present invention, the increase in coercivity is still significantly insufficient if the alloy permeation source is mismatched: Comparative Example 13 uses Pr to replace Ce in the permeation source, lacking a Ce component that matches the cerium-containing matrix, and cannot improve the wettability and interfacial bonding force between the permeation source and the matrix grain boundaries through the low melting point effect of Ce, resulting in a significant increase in the resistance to permeation source diffusion along the grain; Comparative Example 14 uses Al to replace Ga, which cannot effectively reduce the melting temperature of the permeation source, resulting in a significant decrease in the penetration depth and distribution uniformity of heavy rare earth Dy; In Comparative Example 15, the Dy content is too low and the Ce content is too high, resulting in insufficient supply of heavy rare earth and inability to form a sufficient amount of high coercivity shell on the grain surface; In Comparative Example 16, the Dy content is too high and the Ce content is insufficient, which not only wastes heavy rare earth, but also makes it difficult for the permeation source to fully penetrate into the depth of the grain boundaries due to the reduced Ce content, ultimately failing to achieve a significant increase in coercivity. The above results fully demonstrate that the synergistic ratio of Dy, Ce, and Ga in the permeation source is the core factor in ensuring grain boundary diffusion efficiency and uniform distribution of heavy rare earth elements.

[0064] Comparing Example 1 with Comparative Examples 11-12, it can be seen that there is an optimal window for the coating amount of the permeation source; if the coating amount is too low (Comparative Example 12), the supply of heavy rare earth elements will be insufficient, and effective coating cannot be formed; if the coating amount is too high (Comparative Example 11), heavy rare earth elements will easily accumulate locally, which not only wastes materials, but also is not conducive to the uniform improvement of coercivity.

[0065] Comparing Example 1 with Comparative Examples 17-21, it is evident that the two-stage grain boundary diffusion heat treatment process of the present invention has significant advantages. The first stage employs a relatively high-temperature, short-time treatment, which enables the penetration source to rapidly melt and diffuse into the grain boundary. The second stage employs a low-temperature, long-time treatment, which further pushes the diffused heavy rare earth elements from the grain boundary into the grain interior and redistributes them uniformly, effectively solving the problem of low diffusion efficiency caused by the large difference in melting points between the penetration source and the matrix grain boundary. If the temperature or time of the first stage is too high or too long (Comparative Examples 17 and 18), the matrix microstructure will deteriorate due to overheating; if the temperature is too low (Comparative Example 19), rapid melting and diffusion of the penetration source cannot be achieved. If the temperature of the second stage is too high (Comparative Example 21), it will cause excessive diffusion of heavy rare earth elements into the main phase grain interior, resulting in deterioration of the magnet's microstructure; if the temperature of the second stage is too low (Comparative Example 20), the driving force for the diffusion of heavy rare earth atoms is insufficient, and they cannot be fully pushed and uniformly redistributed from the grain boundary to the grain edge.

[0066] Figure 5SEM images a, 5b, and 5c show that the core-shell structure of the infiltrated magnets prepared in Comparative Examples 17, 18, and 19 is significantly inferior to that of Example 1. Figure 1 (b) The shell thickness is relatively thin. This further confirms at the microstructural level that only by combining the specific matrix composition, specific permeation source, and two-stage heat treatment process of this invention can the optimal diffusion efficiency and magnet microstructure be obtained.

[0067] All aspects, embodiments, and features of this invention should be considered illustrative in all respects and not limiting of the invention; the scope of the invention is defined only by the claims. Other embodiments, modifications, and uses will become apparent to those skilled in the art without departing from the spirit and scope of the invention as claimed.

[0068] In the preparation method of this invention, the order of the steps is not limited to the listed order. For those skilled in the art, variations in the order of the steps without creative effort are also within the scope of protection of this invention. Furthermore, two or more steps or actions can be performed simultaneously.

[0069] Finally, it should be noted that the specific embodiments described herein are merely illustrative examples of the invention and are not intended to limit the implementation of the invention. Those skilled in the art can make various modifications or additions to the described specific embodiments or use similar methods to replace them; it is neither necessary nor possible to exemplify all embodiments here. However, these obvious variations or modifications derived from the essential spirit of the invention still fall within the scope of protection of the invention, and interpreting them as any additional limitation would contradict the spirit of the invention.

Claims

1. A method for preparing a cerium-containing magnet with efficient grain boundary diffusion, characterized in that, Includes the following steps: A cerium-containing magnet matrix material is prepared; a permeation source slurry containing permeation source alloy powder is prepared; the permeation source slurry is coated onto the surface of the cerium-containing magnet matrix material to obtain an attached diffusion source magnet; the attached diffusion source magnet is subjected to grain boundary diffusion treatment, and then tempered to obtain the cerium-containing magnet with efficient grain boundary diffusion. The chemical composition of the cerium-containing magnet matrix material is expressed as a weight percentage as [R]. 1-x Ce x ] a M1 b Zr c B d CoeFe 100%-a-b-c-d-e Wherein: 10wt%≤x≤20wt%, 29wt%≤a≤33wt%, 0wt%<b≤0.8wt%, 0.1wt%≤c≤0.3wt%, 0.91wt%≤d≤0.93wt%, 0wt%<e≤1wt%; R is one or both of Pr and Nd, and M1 is one or more of Cu, Ga, and Al; wherein the weight percentages of Fe, Co, B, and Zr satisfy the following relationship: t 1= Fe by weight / 55.845 + Co by weight / 58.933 t2 = (weight parts of B) / 10.811 - 2 × (weight parts of Zr) / 91.224 14.5≤t1 / t2≤15.2; The chemical composition of the permeation source alloy powder, expressed as a weight percentage, is RH. a1 Ce b1 Ga 100%-a1-b1 Where 60wt%≤a1≤75wt%, 10wt%≤b1≤30wt%, 80wt%≤a1+b1≤95wt%, and RH is one or both of Dy and Tb.

2. The preparation method according to claim 1, characterized in that, The amount of the permeation source slurry coating is 0.8 to 1.2 wt% of the weight of the cerium-containing magnet substrate material.

3. The preparation method according to claim 1, characterized in that, The grain boundary diffusion treatment employs a two-stage heating process: the first stage diffusion temperature is 900~950℃, and the holding time is 2~6h; then it is cooled to the second stage diffusion temperature of 800~850℃, and the holding time is 6~12h.

4. The preparation method according to claim 1, characterized in that, The preparation process of the cerium-containing magnet matrix material includes: batching, melting to obtain a casting, hydrogen breaking of the casting to obtain coarse powder, air jet milling to obtain fine powder, orientation molding, and sintering.

5. The preparation method according to claim 1, characterized in that, A permeation source alloy powder, thermoplastic resin binder, and organic solvent are mixed to form a permeation source slurry.

6. The preparation method according to claim 5, characterized in that, Based on the mass of the permeation source slurry, the amount of thermoplastic resin binder added is 2-5 wt%, and the amount of organic solvent added is 10-20 wt%.

7. The preparation method according to claim 1 or 5, characterized in that, The preparation process of the permeation source alloy powder includes: batching, melting to obtain a casting, hydrogen breaking of the casting to obtain coarse powder, and air jet milling to obtain fine powder; the D50 particle size of the permeation source alloy powder is 2~5μm.

8. The preparation method according to claim 5, characterized in that, The thermoplastic resin binder is one or more of polyvinyl butyral, polyvinyl acetal, and polyvinyl alcohol, and the organic solvent is one or more of esters, ketones, and alcohols.

9. The preparation method according to claim 1, characterized in that, The tempering treatment temperature is 460~550℃, and the holding time is 4~8h.

10. A cerium-containing magnet with efficient grain boundary diffusion, characterized in that, It is prepared by any one of the preparation methods described in claims 1 to 9.

Citation Information

Patent Citations

  • Grain boundary diffusion cerium-rich magnet and preparation method thereof

    CN118116718A

  • Method for improving performance of high-abundance cerium magnet

    CN120149051A